PENGENALAN DAN PELATIHAN ALAT MUSIK MARAWIS DI KP. PASAR LAMA DI RT 001 RW 021A DESA SEGARA JAYA, TARUMAJAYA - Putri Amalia; Aningsih Aningsih; Rima Rikmasari (An-Nizam, 2022)
Recognition and Training of Mawaris Musical Instruments in Kp. Pasar Lama at Rt 001 Rw 021A Segara Jaya village, Tarumajaya aims to improve the ability of young people in the art of Mawaris. This activity uses qualitative methods with the type of field research that is descriptive analysis with data collection techniques using observations, interviews and documentation. With this activity, it shows that teenagers can develop and maintain the art of marawis music, practice skills, cohesiveness in a team, shape the character of teenagers who have noble character, as well as the values of politeness to people who are older than us. Through this activity, the participants gain insight into knowledge through the delivery of information related to material on Introduction and Training of Marawis Musical Instruments, thus gaining an understanding of Marawis musical instruments.